2016
DOI: 10.1074/jbc.m116.743815
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 Prevents IL-1β Protein Production by Inhibiting NLRP3 Inflammasome Activation

Abstract: Edited by Luke O'NeillVitamin B6 includes six water-soluble vitamers: pyridoxal (PL), pyridoxamine (PM), pyridoxine (PN), and their phosphorylated forms. Pyridoxal 5-phosphate (PLP) is an important cofactor for many metabolic enzymes. Several lines of evidence demonstrate that blood levels of PLP are significantly lower in patients with inflammation than in control subjects and that vitamin B6 has anti-inflammatory effects, with therapeutic potential for a variety of inflammatory diseases. Although one of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 54 publications
2
80
0
3
Order By: Relevance
“…First, we identified that VitB6 increases AMPK Thr172 phosphorylation in An issue needs to be discussed is that VitB6 has been reported to inhibit inflammation via suppressing NF-κB activation and NLRP3-mediated caspase-1 activation because PLP is able to inhibit the phosphorylation of TAK1 and JNK induced by LPS as well as IKK-IκBα pathway. 9 However, our data reveal that VitB6 inhibits inflammation through AMPK Thr172 phosphorylation followed by DOK3 activation. In consistency, the inactivation of AMPK promotes a state of increased inflammatory responsiveness in murine macrophages, which is demonstrated by activating NF-κB-dependent gene expressions, as well as caspase-1 activation and IL-1β maturation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…First, we identified that VitB6 increases AMPK Thr172 phosphorylation in An issue needs to be discussed is that VitB6 has been reported to inhibit inflammation via suppressing NF-κB activation and NLRP3-mediated caspase-1 activation because PLP is able to inhibit the phosphorylation of TAK1 and JNK induced by LPS as well as IKK-IκBα pathway. 9 However, our data reveal that VitB6 inhibits inflammation through AMPK Thr172 phosphorylation followed by DOK3 activation. In consistency, the inactivation of AMPK promotes a state of increased inflammatory responsiveness in murine macrophages, which is demonstrated by activating NF-κB-dependent gene expressions, as well as caspase-1 activation and IL-1β maturation.…”
Section: Discussionmentioning
confidence: 60%
“…An issue needs to be discussed is that VitB6 has been reported to inhibit inflammation via suppressing NF‐κB activation and NLRP3‐mediated caspase‐1 activation because PLP is able to inhibit the phosphorylation of TAK1 and JNK induced by LPS as well as IKK‐IκBα pathway . However, our data reveal that VitB6 inhibits inflammation through AMPK Thr172 phosphorylation followed by DOK3 activation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As suggested, the gut microbiota can establish efficient crosstalk with the rest of the body through a number of mediators. Interestingly, the metabolic end products of the [41,42] SCFAs [46] miRNAs [56] Indoxyl sulfate [43,44] NO [47] b Bile acids [50] TMAO [45] Vitamin K [51] N E [ 63] Oxalate [48,49] Vitamin B complex [17,[52][53][54] ANS [66,99] Serotonin [62] Threonine [55] ENS [67] GLP-1 [57] GLP-2 [58] PYY [59] GABA [60,61] ACh [65] Dopamine [64] H 2 S [87,88] a Some of these mediators have both pro-and anti-inflammatory effects…”
Section: The Gut Microbiota Regulates Inflammatory Processes Directlymentioning
confidence: 99%
“…On the other hand, the activation of the bile acid receptors Farnesoid X Receptor (FXR) and TGR5 have an anti-inflammatory effect [50], chenodeoxycholic acid (CDCA) being the most potent activator of FXR [83] •NE: Activation of the α-adrenergic receptors elicits pro-inflammatory effects while β-adrenergic receptor activity is anti-inflammatory [63] •ANS: The parasympathetic nervous system (PNS) suppresses inflammation via activation of the ACh receptor α7nAChR [66]. On the other hand, the sympathetic nervous system (SNS) can exert both pro-inflammatory (via α 2 -adrenergic receptors) and anti-inflammatory (via β 2 -adrenergic receptors) effects [66], pro-inflammatory properties being more dominant [99] •ENS: The inflammatory effects of ENS depends on the location of the intestinal macrophages they induce; the lamina propria macrophages (LpMs) are inclined to be pro-inflammatory while the muscularis macrophages tend to have an anti-inflammatory phenotype, having the anti-inflammatory β2-adrenoceptors [67] b Even though NO can have pro-inflammatory activity via NF-κB activation, the number of mechanisms leading to its anti-inflammatory effects are more [47] gut microbiota, including p-CS [41,42]; IS [43,44]; trimethylamine-N-oxide (TMAO) [45]; ammonia [24]; SCFAs [46]; NO [47]; oxalate [48,49] and bile acids [50]; vitamin K [51]; vitamin B complex [17,[52][53][54]; threonine [55]; miRNAs [56]; gut hormones such as GLP-1, GLP-2, and peptide YY (PYY) [57][58][59]; neurotransmitters such as γ-aminobutyric acid (GABA), serotonin, norepinephrine (NE), dopamine (DA), and acetylcholine (Ach) [60][61][62][63][...…”
Section: The Gut Microbiota Regulates Inflammatory Processes Directlymentioning
confidence: 99%